Pembelajaran pendidikan vokasional yang efektif di era revolusi 4.0 di SMK - irwanto irwanto (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to examine comprehensively about effective vocational education based on aspects of the learning process, teaching and school culture. The study used qualitative methods with a descriptive approach. The location of the study at State Vocational High School 2 Serang, Banten. Data analysis techniques use interactive analysis which is data reduction, data presentation and conclusion. The results showed that the Vocational Schools were effective, namely: (1) the school had emphasized active, creative, innovative, fun learning, using interactive multimedia learning, varied learning strategies. The management of classes, workshops and laboratories has been effective because it has been used properly in implementation, especially practice. Learning strategies that are usually used are cooperative, contextual, case studies, discussions, realistic and problem-based learning. (2)The existing culture in the school has been effective in implementing theoretical and practical learning.Work culture like in the Industrial World has been carried out. Projects outside the agency that are carried out by the school are teachers and students to complete the project.The positive work culture of the Industrial World in schools will result in effective theoretical and practical learning and graduates who are qualified and ready to work in the industry.